Study of palmar patterns in diabetic patients - M, Sudagar; K, Radha; K, Duraipandian; KVK, Sundaravadhanam (International Journal of Advances in Medicine, 2017)
Background: Nowadays study of dermatoglyphics has a great importance in judicial and criminal researches. Similarly its study is related to some genetic diseases has an immense applications. Diabetes Mellitus is the silent killer of mankind and public health problem. Therefore investigators are looking for new methods for its early diagnosis and treatment. Dermatoglyphics is a growing discipline and its ease and ready applicability render it as a useful tool to the clinician. Dermatoglyphics may be effectively employed as a screening procedure in future and may help in the early detection of cases of diabetes mellitus. Methods: The present study is undertaken with an aim to evaluate the dermatoglyphic features in diabetic patients. The study consists of 150 diabetic patients and 150 normal healthy individuals as controls. They were 75 males and 75 females in each group. Dermatoglyphic prints were taken by “Ink method” described by Cummins and Midlo and further subjected to statistical analysis to find the variations in the dermatoglyphic features among diabetic patients and control groups. Results: Mean value of a-b ridge count is neither increased nor decreased in diabetic patients (P = 0.852). Mean value of atd angle is slightly decreased in diabetic patients (P = 0.2332). The frequency of t and t’ are increased (P = 0.8462, P = 0.6681) and the frequency of t" is decreased (P = 0.757) in diabetic patients but they are not statistically significant. Conclusion: From the present study, it appears that there do exists a variation in the dermatoglyphic patterns in diabetic patients with an advantage of being simple and economical ‘ink’ method. As the specific features of dermatoglyphic patterns are present in diabetic patients, it can be used for mass screening program to segregate the predicted diabetic patients.